The evolution of high-reliability coordination mechanisms for collision avoidance - Kevin Crowston (The Journal of Information Technology Theory and Application (JITTA), 2003)
Resource sharing and allocation are important coordination problems in most processes and organizations. They are especially critical in transportation systems, where the resource to be shared and allocated is the space through which various vehicles move and the problem is ensuring that vehicles do not conflict in their use of the space—that is, that they do not collide. Transportation systems are interesting because they accomplish this resource allocation in a highly reliable and often highly distributed fashion. In this paper, we apply coordination theory to analyze collision avoidance as a coordination problem. Coordination theory suggests that coordination problems are created by dependencies among activities and resources that constrain how the activities can be performed. To avoid or overcome these constraints, additional work must be performed in the form of a coordination mechanism that manages the dependency. From this perspective, transportation systems can be viewed as collections of mechanisms for allocating a scarce resource, namely the space through which vehicles move. The claim of coordination theory is that having identified the type of dependency involved in transportation systems, we can consider alternative coordination mechanisms and more importantly, the tradeoffs between them. More interestingly, we can analyze how the use of information technology differentially affects the costs of different mechanisms thus shifting the tradeoff. As well, the range of coordination mechanisms identified may have implications for resource allocation in other kinds of organizations.
Keywords: Coordination